Analysis of logistics efficiency in Guangdong and its neighboring provinces based on the DEA-Malmquist index - Yun Wang; Huizhen Jin; Wenbin Qian (PLoS ONE, 2025)
With the development of economic globalization, logistics has become a crucial link in the global supply chain. In the backdrop of growing environmental concerns and the need for more efficient business operations, sustainable logistics and advanced supply chain management have emerged as imperative components. Effective supply chain management.The region centered on Guangdong Province is one of the most active regions in the economic belt, and its geographical, industrial and cultural advantages make it one of the main centers of the national economy. This paper aims to study the regional logistics design centered on Guangdong province, with a special emphasis on incorporating sustainable logistics and supply chain management aspects. It analyzes the current situation and existing problems based on the data envelope analysis (DEA) and Malmquist index model, and conducts the logistics design analysis.The research results show that (1)The technical efficiency and technological progress of Guangdong province and its neighboring provinces have promoted the improvement of its logistics efficiency.(2)The growth of pure technical efficiency is an important factor driving the improvement of logistics efficiency in Guangdong Province and its neighboring provinces.(3)In terms of time evolution,the technological progress index had the least driving effect and should be further strengthened.(4)In 2020, due to the impact of the epidemic, the total factor productivity declined.